Analisis Tingkat Keterampilan Kepemimpinan Atlet Berdasarkan Perspektif Gender Di Sekolah Bulutangkis Provinsi Jawa Barat - Aprillia, Mutiara Sukma; Subroto, Toto; Hambali, Burhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to use quantitative descriptive techniques to examine the level of Leadership Skills possessed by badminton athletes from the West Java Provincial Club. 29 male athletes and 21 female athletes formed a research group of 50 athletes. The instrument used Life Skills Scale of Badminton Sport (LSSBS) developed by (Hambali 2024) consists of 24 items as a means of measuring life skills, and is the instrument used in this study. The researcher created each item to be appropriate and relevant to what will be tested to measure the leadership characteristics possessed by athletes who play badminton. Afterwards, the data was examined using SPSS (Statistical Package For the Social sciences) software version 29.0, independent sample T-test, and descriptive statistical techniques. The researcher showed that male and female athletes have different levels of leadership. With a percentage rate of 62%, both were evaluated in the Moderate group. In terms of gender, male athletes were categorized as Moderate (34%), while female athletes were also classified as Moderate (28%), in the same group. The sig value. (2-Tailed) = 0.020 was revealed by the findings of the independent samples T-test analysis. Conclusion, it can be said that there is a substantial difference in the leadership levels of male and female athletes (sig. (2-Tailed) > 0.05. Keywords: Badminton; Leadership; Life Skills.